Modelling the German system of vocational education - Lindner, Axel [Verfasser] (My University, 1998)
"This paper aims at analyzing main features of the German vocational education. It builds on a simple model of firm specific human capital accumulation in case of learning by doing. A main result is a positive effect of government financed schooling on creating learning by doing jobs. This finding relies on simple strategic arguments and does not depend on long term labor contracts or any cross productivity effects between learning inside and outside the firm. (author's abstract, IAB-Doku) Der Autor analysiert das deutsche duale System im Rahmen eines humankapitaltheoretischen Modells. (IAB)
Keywords: S 4.3.6 Human Capital; L 2.1.3 Erfahrungslernen; L 2.1.1 Informelles Lernen; S 1.3.1 Ausbildung im Dualen System; Humankapitalansatz; On-the-job training; Duales System; Berufsausbildung; Quantitative Angaben